MODEL OF POFITABILITY DETERMINANT FACTORS IN PHARMACEUTICAL SUBSECTOR COMPANIES - Lufriansyah Lufriansyah; Muhammad Irsan (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
This study aims to produce a model of the determinant factors of profitability in pharmaceutical sub-sector companies. While the specific objective: To study the factors that affect the profitability of the pharmaceutical sub-sector company. The population in this study were all pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange, as many as 10 (ten) companies. Sampling in this study using purposive sampling with the criteria of companies that uptade financial reports and can be accessed in the current research year, so that the sample is 6 (six) companies. The type of data used in this research is secondary data. Data is collected through the website www.idx.co.id. The data analysis technique used is descriptive statistical analysis and multiple regression analysis.